The NAC transcription factors play core roles in flowering and ripening fundamental to fruit yield and quality - Liu, Jianfeng; Qiao, Yuyuan; Li, Cui; Hou, Bingzhu (Frontiers in Plant Science, 2023)
Fruits are derived from flowering and play an important role in our food, nutrition and health. In general, flowers determine crop yield and the ripening forms fruit quality. Although transcription factors (TFs) only account for a small part of plant transcriptomes, they control the global gene expression and regulation. The plant-specific NAC (NAM, ATAF and CUC) transcription factors constitute a large of family, evolving concurrently with the transition of both aquatic-to-terrestrial plants and vegetative-to-reproductive growth. Thus, NACs play an important role in fruit yield and quality by shoot apical meristem (SAM) inflorescence determination and ripening control. The present review focuses on the various properties of NACs together with their function and regulation in flower formation and fruit ripening. Hitherto, we have a better understanding of the molecular mechanisms of NACs in ripening through abscisic acid (ABA) and ethylene, but how NACs regulate inflorescence formation-related genes are largely unknown. In the future, we should focus on the analysis of NAC redundancy and identify pivotal regulators in flowering and ripening. NACs are potentially vital manipulation targets for improving fruit quantity and quality.